A Loop-Mediated Isothermal Amplification Assay Utilizing Hydroxy Naphthol Blue (LAMP-HNB) for the Detection of Treponema pallidum Subspp. pallidum - Saranthum Phurijaruyangkun; Pongbun Tangjitrungrot; Pornpun Jaratsing; Suphitcha Augkarawaritsawong; Khurawan Kumkrong; Sawanya Pongparit; Pawita Suwanvattana; Supatra Areekit; Kosum Chansiri; Somchai Santiwatanakul (Pathogens)
Treponema pallidum subspp. pallidum is a spirochaete bacterium that causes syphilis, one of the most common sexually transmitted diseases. Syphilis progresses through four distinct stages, each characterized by specific symptoms, namely primary, secondary, latent, and late (tertiary) syphilis. Serology has been considered the primary diagnostic approach. However, it is plagued by problems such as the limited specificity of nontreponemal tests and the inadequate correlation of treponemal tests with disease activity. In this study, we focused on the development of a loop-mediated isothermal amplification assay utilizing hydroxy naphthol blue (LAMP-HNB) for the diagnosis of T. pallidum subspp. pallidum. Specifically, this study seeks to determine the analytical sensitivity (limit of detection; LOD) and analytical specificity. Four hundred clinical serum samples were analyzed for diagnostic sensitivity, specificity, and predictive value, and each technique’s 95% confidence intervals (95% CI, p < 0.05) were evaluated. The limit of detection for polymerase chain reaction with agarose gel electrophoresis (PCR-AGE), the loop-mediated isothermal amplification assay combined with agarose gel electrophoresis (LAMP-AGE), and LAMP-HNB were 116 pg/µL, 11.6 pg/µL, and 11.6 pg/ µL, respectively. Analytical specificity examinations indicated the absence of cross-reactivity with Leptospira interrogans, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, human immunodeficiency virus (HIV), and healthy human serum in PCR-AGE, LAMP-AGE, and LAMP-HNB. The diagnostic sensitivity, diagnostic specificity, positive predictive value (PPV), and negative predictive value (NPV) for PCR-AGE were 100.00 (100.00)%, 94.50 (94.40–94.60)%, 94.79 (94.69–94.88)%, and 100.00 (100.00)%, respectively. While, for LAMP-AGE and LAMP-HNB, they were 100.00 (100.00)%, 91.00 (90.87–91.13)%, 91.74 (91.63–91.86)%, and 100.00 (100.00)%, respectively. The LAMP-HNB test is simple, rapid, highly sensitive, and highly specific, without requiring expensive equipment. In the future, the LAMP-HNB assay may develop into a single-step diagnostic process, enabling the use as point-of-care testing for the diagnosis, prevention, and management of syphilis infection.